ESTADO DEL CONOCIMIENTO Y CONSERVACIÓN DE LOS COLEÓPTEROS SCARABAEOIDEA (INSECTA) DEL ESTADO DE HIDALGO, MÉXICO - Delgado, Leonardo; Márquez, Juan (Instituto de Ecología, A.C., 2006)
A faunistic and conservation-oriented analysis of the Scarabaeoidea beetles from the Hidalgo State, México is presented. Seven families with 95 genera and 276 species are recorded, of which five genera and six species are considered introduced. Fifteen species are cited for the first time for this state and 21 species are considered to be erroneously or doubtfully recorded for Hidalgo. Thus, Hidalgo is the fifth Mexican state with the highest number of Scarabaeoidea species. On the basis of estimates of species numbers of several biological groups, it is extrapolated that at least 100 species are missing to record from this state. According to the geographical distribution of the species, six groups are proposed (with the exception of introduced species): endemic from Hidalgo (13 spp.), endemic from México (104 spp.), North American (37 spp.), Central American (55 spp.), Latin American (32 spp.), and American (29 spp.).With respect to the vegetation types of the state, the coniferous forest has 92 species of which 37 are restricted to this forest, the oak forest 71 species and none are restricted, the cloud forest 108 species with 34 restricted, the tropical evergreen and semideciduous forests 108 species with 29 restricted, the tropical deciduous forest 69 species with one restricted, and the xerophilous scrub 52 species with 12 restricted. The distribution of the species by biogeographical provinces shows that 62.1 % of the total species are exclusively located in the Sierra Madre Oriental, 13.8 % in the Altiplano Mexicano, 3.8 % in the Eje Neovolcánico Transmexicano and 1.9 % in the Golfo de México. With regard to endemism of Hidalgo and México, the coniferous forest presents 60 species, the cloud forest 59 species, the oak forest 44 species, the tropical evergreen and semideciduous forests 16 species, the xerophilous scrub 13 species, and the tropical deciduous forest nine species.With regard to the four federal protected natural areas of the Hidalgo state, it is necessary to carry out a systematic faunal work at the Biosphere Reserve Barranca de Metztitlán, due to the lack of data of scarab beetles from this and many other arid and semiarid areas of México. It is also important to complete the faunal inventories of the areas with coniferous and oak forests, among them the National Parks Los Mármoles and El Chico. In addition, it is advisable to conduct supplementary collections in areas with tropical deciduous forest, since information on scarab beetles in this forest in Hidalgo state is scarce. On the basis of the high values of richness, endemism and restricted species numbers of the scarab beetles inhabiting the cloud forests, it is urgent to propose protected areas in the state of Hidalgo with this type of vegetation. It is also necessary to obtain more information on the eco-geographical distribution of scarab beetles from Hidalgo, in order to propose species into categories of risk. Likewise, the present-day number of protected natural areas is considered inadequate to preserve this insects group.